1979
DOI: 10.1073/pnas.76.11.5948
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of herpes simplex virus type 2 from a quiescent state by human cytomegalovirus.

Abstract: The ability of human cytomegalovirus to stimulate replication of herpes simplex virus type 2 (HSV-2) was examined. The system used involved HSV-2-infected human embryonic lung cells under conditions (39.5-40°C) in which HSV-2 remains undetectable. Reactivation of HSV-2 was maximal and persisted for the longest duration when cultures were superinfected with 0.02 plaque-forming unit of human cytomegalovirus per cell. Infectious HSV-2 appeared 2 days after superinfection with human cytomegalovirus and ranged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…HCMV was as efficient as HSV-1 ts mutants, in agreement with previous findings in a related in vitro latency system (Colberg-Poley et al, 1979, 1981Wigdahl et al, 1981); the virus produced was identified as HSV-2 by its ability to form plaques on BHK cells, which are non-permissive for HCMV (results not shown). By contrast, adenovirus type 2 (Ad2) or type 5 (Ad5), or tsK which had been irradiated with u.v.…”
supporting
confidence: 80%
“…HCMV was as efficient as HSV-1 ts mutants, in agreement with previous findings in a related in vitro latency system (Colberg-Poley et al, 1979, 1981Wigdahl et al, 1981); the virus produced was identified as HSV-2 by its ability to form plaques on BHK cells, which are non-permissive for HCMV (results not shown). By contrast, adenovirus type 2 (Ad2) or type 5 (Ad5), or tsK which had been irradiated with u.v.…”
supporting
confidence: 80%
“…human cytomegalovirus (Colberg-Poley et al, 1979. We have selected and isolated HSV genomes lacking XbaI sites normally present (Brown et al, 1984;Harland & Brown, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Reports that ACV in combination with human IFNs produces at least additive inhibitory effects on HCMV replication (17,28) prompted our investigation of the combined use of ACV and IFN-a in plaque reduction and replication kinetic assays. Since ara-A combined with IFNa or BVDU has been shown to act in a synergistic manner to inhibit HSV (16,27) were grown in Dulbecco medium containing 10%o heatinactivated fetal calf serum as previously described (6,7,30). Maintenance medium contained 5% fetal calf serum with supplements as previously described (6,7).…”
mentioning
confidence: 99%